Structure, dynamics and primitive path network of polymer nanocomposites containing spherical nanoparticles. Issue 1619 (13th March 2014) - Karatrantos, Argyrios; Clarke, Nigel; Composto, Russel J.; Winey, Karen I.
ABSTRACT We investigate the effect of nanoparticles on polymer structure, polymer dimensions and topological constraints (entanglements) in polymer melts for nanoparticle loading above percolation threshold as high as 40.9% using stochastic molecular dynamics (MD) simulations. We show unambiguously that short polymer chains are not disturbed by the presence of repulsive nanoparticles. In contrast entangled polymer chains can be perturbed by the presence of attractive nanoparticles when the polymer radius of gyration is larger than the nanoparticle radius. They can expand under the presence of attractive nanoparticles even at low nanoparticle loadings of very small nanoparticle size. We observe an increase in the number of entanglements (decrease of Ne with 40.9% volume fraction of nanoparticles dispersed in the polymer matrix) in the nanocomposites as evidenced by larger contour lengths of the primitive paths. Attraction between polymers and nanoparticles affects the entanglements in the nanocomposites and alters the primitive path.